Food–Drug Interactions: Effect of Propolis on the Pharmacokinetics of Enrofloxacin and Its Active Metabolite Ciprofloxacin in Rabbits - Ali Sorucu; Cengiz Gokbulut; Busra Aslan Akyol; Osman Bulut (Pharmaceuticals, 2025)
Propolis is a natural resinous substance produced by honeybees that has many biological activities. For thousands of years, it has been widely used as a dietary supplement and traditional medicine to treat a variety of ailments due to its antimicrobial, anti-inflammatory, antioxidant, immunomodulatory, and wound-healing properties. Nutritional supplements and foods may interact with drugs both pharmacodynamically and pharmacokinetically, which could raise clinical concerns. Background/Objectives: This study aimed to investigate the effect of propolis on the plasma disposition of enrofloxacin and to assess the potential pharmacokinetic interaction in rabbits. Methods: In this study, enrofloxacin was applied per os (20 mg/kg) and IM (10 mg/kg) and with propolis (100 mg resin/kg) administration in four groups of rabbits (each of six individuals). Heparinized blood samples were collected at 0, 0.1, 0.3, 0.5, 1, 2, 4, 8, 12, and 24 h post-administration. HPLC-FL was used to analyze the plasma concentrations of enrofloxacin and its active metabolite ciprofloxacin following liquid–liquid phase extraction, i.e., protein precipitation with acetonitrile and partitioning with sodium sulfate. Results: The results revealed that propolis coadministration significantly affected the plasma disposition of enrofloxacin and its active metabolite after both per os and intramuscular administration routes. Significantly greater AUC (48.91 ± 11.53 vs. 26.11 ± 12.44 µg.h/mL), as well as longer T1/2λz (11.75 ± 3.20 vs. 5.93 ± 2.51 h) and MRT (17.26 ± 4.55 vs. 8.96 ± 3.82 h) values of enrofloxacin and its metabolite ciprofloxacin, were observed after the coadministration of propolis compared to enrofloxacin alone following both per os and IM routes in rabbits. Conclusions: The concurrent use of propolis and prescription medications may prolong the half-life (T1/2λz) and increase the systemic availability of chronically used drugs with narrow therapeutic indices. The repeated use of drugs such as antibiotics, heart medications, and antidepressants, or drugs with a narrow therapeutic index such as antineoplastic and anticoagulant agents, can cause toxic effects by raising blood plasma levels. Considering the varied metabolism of rabbits and humans, further validation of this study may require thorough clinical trials in humans.